Capital ships at war 1939-1945 - Mace, Martin; Grehan, John (Despatches from the front, 2014)
Despatches in this volume include those relating to the sinking of the German battleship Graf Spee in the Battle of the River Plate in 1939, the loss of the battleships HMS Prince of Wales and HMS Repulse in the Far East, the sinking of the German battle cruiser Scharnhorst in 1943, the attack on Tirpitz by midget submarines, the contribution by British Pacific Fleet to the assault on Okinawa in 1945 (which included four Royal Navy battleships), and the sinking of Bismarck in 1941.